The Comparison of Total Drain Volume in Post MRM Patient Using Songket Design and Tewart Design in Dr. Mohammad Hoesin General Hospital Palembang - Meigi Medika; Nur Qodir (Sriwijaya Journal of Surgery, 2020)
Background: In 2018, breast cancer was the most common malignancies in women. Which main modality for the management is surgery. The most frequently-used incision design is Stewart incision. Its disadvantages were difficult to access axillary, surgical scar, lateral ear dog and the loss of anterior axillary fold. Another design used is Songket design which consists of crescent incision, rule of half buried mixed mattress suture technique and axillary anker suture. This study aims were to compare the total drain volume of post-MRM breast cancer patients between Songket and Stewart incision design. Method: Clinical randomized control trial (cRCT) research is the most robust design for evaluating the interventions used. Samples were all post-Modified Radical Mastectomy Ca Mammae patients with Songket and Stewart incision design who were hospitalized in the Department of Surgery at Dr. Mohammad Hoesin Hospital Palembang in the time of June - November 2019. The inclusion criteria were Ca Mammae patients who underwent the procedure and agreed to participate for this study. The patients who had post-operative wound dehiscence, under-documented drains, or the history of axillary lymph node surgery were excluded from this study. Results: Total drain volume for post-MRM using Stewart incision was 613.85 ± 215.93 ml, while Songket Incision stood was 116.15 ± 139.95 ml. The mean age of the study subjects was 48.69 ± 9.57. BMI was 23.65 ± 3.51 on average. Total drain volume of Stewart incision design was 497.7 ± 75.98 higher than Songket incision design. Conclusion: There was found significant difference in total drain volume between the two groups with p value of <0.001.